Applications of neutrosophic complex numbers in triangles - Yaser Ahmad Alhasan; Iqbal Ahmed Musa; Isra Abdalhleem Hassan Ali (Neutrosophic Sets and Systems, 2023)
It may be difficult for researchers to memorize or remember the trigonometric ratios of any neutrosophic angle, and this is what prompted us to activate the role of the neutrosophic complex numbers for that. In this paper we presented neutrosophic Euler’s formulas and neutrosophic De Moivre's formula. Also, we benefited from that by finding the trigonometric ratios of the multiples of neutrosophic angle in terms of the trigonometric ratios of the neutrosophic angle (𝜃̈+ 𝜑̈𝐼) and convert trigonometric ratios from formula 𝑠𝑖𝑛𝑛(𝜃̈+ 𝜑̈𝐼), or formula 𝑐𝑜𝑠𝑚(𝜃̈+ 𝜑̈𝐼), into a linear expression for the multiples of the neutrosophic angle (𝜃̈+ 𝜑̈𝐼), which made it easier for us to find integrals of the neutrosophic trigonometric functions by other methods.